Introduction to Special Issue on Increasing Participation in Higher Education STEM Programs - Susan Staats; Amy Lee (MDPI AG, 2020)
This special issue highlights the work of several higher education practitioner-scholars who describe their approaches to facilitating participation in STEM courses and programs. Writing from the standpoint of chemistry, mathematics, and ecology in publicly supported universities, the authors discuss their pedagogical or curricular choices with reference to the broader structures and systemic considerations that sometimes limit and sometimes enable faculty effort. In this editorial, we reflect on the ways in which these authors invoke their own practitioner agency to establish equity-based innovations in higher education STEM settings.